Substrate inhibition by the blockage of product release and its control by tunnel engineering. Issue 2 (11th January 2021) - Kokkonen, Piia; Beier, Andy; Mazurenko, Stanislav; Damborsky, Jiri; Bednar, David; Prokop, Zbynek
Abstract : Substrate inhibition can be caused by substrate binding to the enzyme–product complex and can be controlled rationally by targeting enzyme access tunnels. Abstract : Substrate inhibition is the most common deviation from Michaelis–Menten kinetics, occurring in approximately 25% of known enzymes. It is generally attributed to the formation of an unproductive enzyme–substrate complex after the simultaneous binding of two or more substrate molecules to the active site. Here, we show that a single point mutation (L177W) in the haloalkane dehalogenase LinB causes strong substrate inhibition. Surprisingly, a global kinetic analysis suggested that this inhibition is caused by binding of the substrate to the enzyme–product complex. Molecular dynamics simulations clarified the details of this unusual mechanism of substrate inhibition: Markov state models indicated that the substrate prevents the exit of the halide product by direct blockage and/or restricting conformational flexibility. The contributions of three residues forming the possible substrate inhibition site (W140A, F143L and I211L) to the observed inhibition were studied by mutagenesis. An unusual synergy giving rise to high catalytic efficiency and reduced substrate inhibition was observed between residues L177W and I211L, which are located in different access tunnels of the protein. These results show that substrate inhibition can be caused by substrate binding to the enzyme–product complex and can be controlled rationally by targeted amino acid substitutions in enzyme access tunnels.